2012
DOI: 10.1001/archophthalmol.2011.2573
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal and Nocturnal Variations in Aqueous Humor Dynamics of Patients With Ocular Hypertension Undergoing Medical Therapy

Abstract: To evaluate the interaction of intraocular pressure (IOP)-lowering medications with physiologic day and night changes in aqueous humor dynamics in participants with ocular hypertension.Methods: Thirty participants were enrolled in this double-masked, randomized, crossover study. Each participant underwent aqueous humor dynamics measurements at baseline and at 2 weeks of dosing in random order with latanoprost in the evening and placebo in the morning, timolol maleate twice daily, and dorzolamide hydrochloride … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 43 publications
1
40
0
1
Order By: Relevance
“…If prostaglandin analogs increase uveoscleral flow by a percentage, rather than by a fixed amount, then the nocturnal effect on absolute uveoscleral flow rate would be small, because uveoscleral flow is markedly reduced at night. This small change in absolute uveoscleral flow rate would be more difficult to detect, consistent with the findings of Gulati et al 48 In contrast, outflow facility decreased by only approximately 15% at night in our subjects, which suggests that improving outflow facility may be a possible mechanism for reducing nocturnal IOP. It is possible that prostaglandin analogs, which have persistent nocturnal efficacy, may use this mechanism.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…If prostaglandin analogs increase uveoscleral flow by a percentage, rather than by a fixed amount, then the nocturnal effect on absolute uveoscleral flow rate would be small, because uveoscleral flow is markedly reduced at night. This small change in absolute uveoscleral flow rate would be more difficult to detect, consistent with the findings of Gulati et al 48 In contrast, outflow facility decreased by only approximately 15% at night in our subjects, which suggests that improving outflow facility may be a possible mechanism for reducing nocturnal IOP. It is possible that prostaglandin analogs, which have persistent nocturnal efficacy, may use this mechanism.…”
Section: Discussionsupporting
confidence: 89%
“…[41][42][43][44] Prostaglandin analogs, however, may reduce pressure through two actions, one that improves outflow facility (although this has not been a universal finding) and the other that increases uveoscleral flow. [45][46][47] A study by Gulati et al 48 suggested that latanoprost might increase uveoscleral outflow at night, although their study was not sufficiently powered to show a statistically significant difference. If prostaglandin analogs increase uveoscleral flow by a percentage, rather than by a fixed amount, then the nocturnal effect on absolute uveoscleral flow rate would be small, because uveoscleral flow is markedly reduced at night.…”
Section: Discussionmentioning
confidence: 99%
“…Gulati V et al, conducted a double masked, randomised, cross over study to evaluate the interaction of antiglaucoma drugs with physiologic day and night changes in aqueous humor dynamics in ocular hypertensive patients [17]. It showed that Latanoprost is better than Timolol in reducing night time intraocular pressure.…”
Section: Discussionmentioning
confidence: 99%
“…In doing so, prostaglandin analogues are recommended as the first-line choice of medical treatment since they reduce both daytime and nighttime IOP. 36 Topical beta-blockers should be avoided in these patients as they have the potential for significant systemic side effects including nocturnal hypotension that may be harmful to some NTG patients. 37 Notably, poorer baseline VF function was a significant glaucoma progression predictor in our study population.…”
Section: Determination Of Factors Associated With Visual Field Progrementioning
confidence: 99%